Barriers to participation in a placebo-surgical trial for lumbar spinal stenosis. Issue 5 (May 2019) - Anderson, David B.; Mobbs, Ralph J.; Eyles, Jillian; Meyer, S. Eileen; Machado, Gustavo C.; Davis, Gavin A.; Harris, Ian A.; Buchbinder, Rachelle; Ferreira, Manuela L.
Abstract: Background: Placebo-controlled trials are an important tool when assessing the efficacy of spinal surgical procedures. The most common spinal surgical procedure in older adults is decompression for lumbar spinal stenosis. Before conducting a placebo-surgical trial on decompression surgery, an investigation of patients' willingness to participate in a placebo-controlled trial of decompression surgery and barriers to participation were explored. Materials: An online survey. Methods: Descriptive analyses of demographic and clinical data, and participants' willingness to participate in a placebo-surgical trial. Logistic regression was used to examine potential predictors of willingness to participate. Two independent researchers performed a coded framework analysis of patients' barriers to participation. Results: 68 patients were invited and 63 participants completed the survey (91.3% response, mean (SD) age 69.5 (10.9) years, 52% females), 71% suffered from moderate to very severe pain. Ten participants (15.9%) were willing to participate in a placebo-controlled trial. Being married was associated with decreased odds of participating (OR: 0.2; 95% CI, 0.05 to 0.8; P = 0.03), while the main barriers were a lack of information about the procedure, reassurance of a positive outcome with participation, and concerns about the risks and benefits of placebo surgery. Conclusions: A minority of patients with lumbar spinal stenosis were willing to participate in a placebo-controlled trial of surgery. The identified barriers indicate that educating eligible patients about: the need for placebo-surgical trials, the personal risks and benefits of participation, and the importance and potential benefits of placebo trials to others, may be crucial to ensure adequate recruitment into the placebo-controlled surgical trial. Conclusions should be read cautiously however, given the small sample size present in this study.